2020
DOI: 10.21203/rs.3.rs-64083/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Prognosis Model for Predicting Survival in Severe and Critically Ill COVID-19 Patients Using Machine Learning

Abstract: Background Novel coronavirus disease (COVID-19) is an emerging, rapidly evolving situation. At present, the prognosis of severe and critically ill patients has become an important focus of attention. We strived to develop a prognostic prediction model for severe and critically ill COVID-19 patients.MethodsTo assess the factors associated with the prognosis of those patients, we retrospectively investigated the clinical, laboratory characteristics of confirmed 112 cases of COVID-19 admitted between 21 January t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…25 studies 33–57 out of 1,008 identified publications were incorporated according to the inclusion criteria (Figure 1; Table 1). 19 articles were peer‐reviewed and 6 were preprints 35–37,40,45,53 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 studies 33–57 out of 1,008 identified publications were incorporated according to the inclusion criteria (Figure 1; Table 1). 19 articles were peer‐reviewed and 6 were preprints 35–37,40,45,53 .…”
Section: Resultsmentioning
confidence: 99%
“…25 studies 33–57 out of 1,008 identified publications were incorporated according to the inclusion criteria (Figure 1; Table 1). 19 articles were peer‐reviewed and 6 were preprints 35–37,40,45,53 . While nine articles evaluated RDW on admission to assess the severity of COVID‐19 patients, others addressed RDW on admission between survivors and non‐survivors.…”
Section: Resultsmentioning
confidence: 99%